2018
DOI: 10.1590/s1980-220x2017023203342
|View full text |Cite
|
Sign up to set email alerts
|

Fatores preditores de óbito em Unidade de Terapia Intensiva: contribuição para a abordagem paliativista

Abstract: RESUMO Objetivo Identificar preditores de óbito na Unidade de Terapia Intensiva e relacionar pacientes elegíveis para cuidados paliativos preferenciais. Método Coorte prospectivo que avaliou pacientes internados por mais de 24 horas, subdivididos em G1 (pacientes que morreram) e G2 (pacientes com alta hospitalar). Para a identificação dos fatores preditores para o desfecho óbito, foi feita ao médico intensivista a “pergunta-surpresa” e foram coletados dados clínico-demográficos dos pacientes. Os dados fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
0
7
0
13
Order By: Relevance
“…14 Thus, the use of technologies available in the ICU environment, as a healing mechanism for patients with therapeutic restrictions, often promotes the prolongation of death. 14,19 CNCDs, in general, are also associated with four main risk factors: cigarette use, lack of physical activity, inadequate diet and harmful consumption of alcoholic beverages. 16 In this study, 24 (54.5%) participants were smokers and 18 (40.9%) alcoholics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Thus, the use of technologies available in the ICU environment, as a healing mechanism for patients with therapeutic restrictions, often promotes the prolongation of death. 14,19 CNCDs, in general, are also associated with four main risk factors: cigarette use, lack of physical activity, inadequate diet and harmful consumption of alcoholic beverages. 16 In this study, 24 (54.5%) participants were smokers and 18 (40.9%) alcoholics.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, knowing how CNCDs behave, risk factors, the occurrence of hospitalizations, among other factors, is essential to guide planning and decision-making. 19 PC are a response applied to the imbalances resulting from chronic, progressive diseases, intending to prevent the suffering generated by them, providing quality of life to patients and their families. 19 However, electing patients who fit the PC criteria is a challenge.…”
Section: Resultsmentioning
confidence: 99%
“…Women are often affected by work overload, as some do not allow time for self-care. [7][8][9] It should be noted that the number of days of hospitalization in this study had a minimum of one day (less than 24h) and a maximum of 79 days, with an average time of 17 days and, compared to the literature, one study brought as permanence dependent on factors, such as the type of underlying disease and the therapeutic requirements of each patient. 10 In another study, it was found that there is no consensus regarding length of stay, given the variation in the profile of patients who are received in the sector (clinical and surgical), and it is important to consider the clinical conditions, presence of possible complications or improvement that may interfere relatively in the length of ICU stay.…”
Section: Resultsmentioning
confidence: 99%
“…A study that aimed to identify predictors of death in the ICU and to relate patients eligible for preferential palliative care, demonstrates that a portion of patients who are admitted to the ICU would need a palliative assessment and approach from the moment of their admission, so that therapeutic limits can be established and avoid false hopes for family members and the team that assists this patient (3) . The practice of palliative care performed in team, with a multidisciplinary and interdisciplinary character is the result of an approach focused on the human being in its entirety, aiming to satisfy the needs of a physical, social, emotional and spiritual nature (1) .…”
Section: Introductionmentioning
confidence: 99%